National Service for Health : the Labour Party's post-war policy (London : Labour Party)
1943-04 1943 1940s 24 pages We said that the system must offer a fair deal to doctor and patient alike; but we found that only a system of whole-time, salaried, and pensionable doctoring would meet these requirements. We said that in the interests of true economy certain Services, such as the School Medical Service and the various Services connected with maternity and infancy, need expansion; only the community can provide for this expansion. So it comes to this : Do you, as a citizen, want a Medical Service that is planned and directed in accordance with the needs of the nation as a whole ; or do you think that we had better muddle along with the present system, distorted as it is by the influence of private profit? Do you not agree with the Labour Party that the Medical Service should be developed, as rapidly as conditions permit, into a State Medical Service, as part of a comprehensive National Service for Health? PART II A STATE MEDICAL SERVICE Assuming that a State Medical Service is needed, how should it be organised? What services should it render? Could the nation afford it? Here, in brief, is the Labour Party's answer. CHAPTER IV LABOUR'S PLAN FOR A STATE MEDICAL SERVICE The nation's most precious asset — its health — is to be insured by the entire nation. So the nation must have, amongst other services, a State Medical Service which is sensibly planned so as to make the very best use of all the nation's medical resources for the benefit of all. Organisation There must, therefore, be some Central Health Authority, competent to plan the Health Services as a whole, including the Medical Service, subject to the general control of Parliament, and competent to see that the plan is carried out, with due allowance for the diversity of local conditions. There must also be some kind of Regional Authority, for the more detailed planning of the medical service and for its administration. Besides this, there must be local units, under the general administration of the Regional Authority. Some of these operational units should be large enough to allow for the concentration of medical equipment and specialists at convenient centres, others should be small enough to make the service easily accessible to everyone who needs it. 14 36/H24/40